Gastroesophageal Reflux Disease and Coronary Heart Disease: Is There a “Mutual Burden” Syndrome? - O. P. Alekseeva; D. V. Pikulev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. This review aims to generalize data on the mutual aggravating effect on the course of gastroesophageal reflux disease (GERD) and coronary heart disease (CHD).General findings. The combination of CHD and GERD is a common clinical situation. In recent years, more and more information has appeared indicating a non-accidental character of the comorbidity of both diseases. In addition to common risk factors, a number of pathophysiological mechanisms have been established that determine a pathogenetic relationship between CHD and GERD. Reflux disease contributes adversely to chronic coronary heart disease, e.g. by increasing the risk of developing myocardial infarction (MI). The co-occurrence of myocardial ischemia episodes (registered by ECG) with those of heartburn has been identified. A correlation between pathological reflux and ST segment depression has been found. A trigger role of reflux in relation to angina attacks and heart rhythm disturbances has been determined. The pro-arrhythmic effects of GERD on the myocardium are explained by an imbalance of the autonomic nervous system with a predominance of the parasympathetic tone. In turn, both stable angina and myocardial infarction contribute to a more aggressive and refractory course of reflux esophagitis (RE), thus triggering reflux symptoms.Conclusion. The comorbid course of coronary heart disease and GERD is based on complex associations; this clinical situation is characterized by a mutual burden syndrome. Given the high prevalence of a combination of both diseases, it seems relevant to develop pathogenetically substantiated approaches to the management of this category of patients.